When Agnes caws - Fleming, Candace (Atheneum Books for Young Readers, 1999)
When eight-year-old Agnes Peregrine, an accomplished birdcaller, travels with her parents to the Himalayas in search of the elusive pink-headed duck, she encounters a dastardly foe.